Analysis of vegetation in recharge area as climate change mitigation for conserving water springs in Keduang Sub-Watershed. Issue 1 (July 2021) - Yuliantoro, D; Budiastuti, M T S; Mujiyo
Abstract: Keduang Sub-Watershed is one of the priority watershed experiencing drought. Drought occurs due to the lack of water resources. The water resources are mostly affected by the climate change phenomenon, causing precipitation by the raising of temperature. The effort of water springs conservation is needed to maintain the existence of water springs. Agroforestry on recharge area was a mitigation effort of the water springs conservation. Mitigation activity for conserving water springs is begun by vegetation analysis in recharge area, relating to the frequency, density, dominance, and the important value index (IVI) of the species. The existence of vegetation in the recharge area has functioned as a protector and regulator of the water system. The study aims to identify the type of vegetation in the recharge area in the Keduang sub-watershed. It was conducted by taking data of all vegetation. The method of the study was a swath line, with a swath measurement of 20m x 20m used to collect data of tree, 10m x 10m to collect data of pole, and 5m x 5m to collect data of seedling. The data were analyzed by analysis of vegetation to get the frequency, density, dominance, and the IVI of species. The result showed that the type of vegetation in the recharge area in the Keduang sub-watershed has an important score of more than 10% consisting of 5 classes. The important score showed that Jati ( Tectona grandis ) as a tree was the highest followed by Sengon (Albizia falcataria ) as a pole, and Johar ( Cassia Siamea ) as a seedling.